A Quality Improvement Project on Evaluating factors for Cancellation of Ophthalmic surgery. - Zeb, Amir; Nazneen, Zainab; Saleem, Wishal; Ilyas, Zainab; Ameen, Usman; Ashfaq Shah, Zarnam; Sajid Kazmi, Hassan (Biological and Clinical Sciences Research Journal, 2025)
Ongoing challenges with surgery cancellations impose pressure on the healthcare system, necessitating systematic reforms to enhance efficiency, resource allocation, and patient care. Consequently, this audit aimed to assess the extent of cancelled cases and identify the underlying causes for their cancellation in a tertiary care hospital. Objective: To assess the frequency of cancelled surgical cases and identify the contributing factors in a tertiary care hospital. Methods: This study was carried out from January 1, 2023, to December 31, 2023, over two sessions. During this timeframe, a comprehensive census was conducted of all cases on the operating theatre (OT) list. Data from both sessions were collected using a structured proforma and analysed with SPSS version 23. Results: 81 (11.80%) cancellations were recorded from the total cases on the OT list. The median age with the interquartile range was 27 (52.5) years. In the first cycle, 17 (43.6%) of the cancellations occurred due to medical reasons, 15 (38.5%) did not show up, 1 (2.6%) experienced a change in plan, and no case was cancelled due to equipment malfunction. In the second cycle, out of the cancelled cases, approximately 17 (40.5%) were due to medical reasons, 6 (14.3%) did not show up, 08 (19%) experienced a change in plan, and 2 (4.8%) was due to equipment failure, with a statistically significant difference noted between the reasons in the first and second cycles (p=0.01). Conclusion: This study indicates that many of the factors contributing to the cancellation of surgeries are preventable, and adhering to guidelines can substantially decrease the number of cancelled cases.